M-3 INSTRUCTIONAL MODEL: MUNAZHARAH, MUDZAKARAH, AND MUHASABAH - Syihabuddin, Syihabuddin (UPI Press, 2013)
The article presents the outcome of research on 30 books of Quranic interpretations for sura al-Ghasyiah, verses 17-26, which are strongly assumed to contain pedagogic meanings, concepts,and values that can be formulated into an instructional model. The research was conducted byanalyzing the keywords of the verses lexically, contextually, and hermeneutically. Then, themeanings gained were categorized, compared, contrasted, and abstracted, so that they wereeventually synthesized into a main idea as a hypothetical model, termed M-3 Model. Themodel consists of three main instructional activities, represented in the terms munazharah,mudzakarah, and muhasabah. The three activities are a mutually completing and supportingcycle for the achievement of various instructional objectives, ultimately to improve the abilityand skills of students to think systematically, logically, creatively, and innovatively throughthe development of potentials and fi trah (human norm). Specifi cally, munazharah activity isexpected to result in cognitivistic knowledge (ainal yaqin), mudzarakah to develop knowledge,experience, and values into faith-based knowledge (‘ilm al-yaqin), and muhasabah to encouragethe achievement of knowledge and values whose truths have been proven (haqqul yaqin), sothat they will be the driving force for various activities based on law, moral, and ethics.Because the model taught by God to human beings is still hypothetical and theoretical in nature,it is suggested that the model be empirically tested to be more valid.Keywords: Instructional Model, Munazharah, Mudzakarah, Muhasabah